Evaluation of the Scenarios of Mergers and Acquisitions in Brazil: (Avaliação Dos Cenários Das Fusões E Aquisições No Brasil) (International Journal of Scientific Research and Management (IJSRM), 2024)
Context -Mergers and Acquisitions (M&A) are strategies that seek to conquer new markets, acquire technology, increase its portfolio of customers and products. The prospective scenario methodology aims to assist companies in making corporate decisions. Purpose -Within this context, and in an unprecedented way, the research presents a model for evaluating events for the scenarios of mergers and acquisitions planned for Brazil in the period from 2017 to 2026. Method - We used a descriptive research method, with the Multi technique -Attribute Global Inference of Quality [MAGIQ] and content analysis techniques. Conclusion - The products generated from the research were the ranking table of the global weights of the sub-factor factors and the proposal of a methodology for evaluating the events in the scenarios based on a likert scale of four points in addition to a model form for evaluation and guidance for the development of scenarios.